Chemistry Learning Innovation in Household Level Entrepreneurship Product Training for The Community of Tidung Island - Familia Novita Simanjuntak; Nova Irawati Simatupang; St Fatimah Azzahra; Sumiyati Sumiyati; Nelius Harefa; Elferida Sormin; Leony Sanga Lamsari Purba (Universitas Negeri Medan, 2024)
This community service aims to provide support and training to PKK women on Tidung Island. Service implementation is carried out using presentations, interactive discussions, and direct practice to improve the village's capacity and creativity. The objectives to be achieved by this activity are to increase knowledge about the effects of careless disposal of used cooking oil waste and to improve skills in handling used cooking oil so that it is a valuable useful treatment. Used cooking oil is waste cooking oil that has been used many times and contains carcinogenic compounds that are difficult to decompose. Both of these properties are dangerous to health and the environment if used cooking oil is consumed and discharged into the environment without change. To achieve this goal, the method that will be used in this activity is to provide health education on the effects of careless disposal of used cooking oil waste and subsequent processing practices using cooking oil into candles. The outcome of undertaking this activity is an increased understanding of the impact of used cooking oil waste on health and the environment. In addition, you can also take advantage of used cooking oil scraps to make candles.